Morphometric and phytochemical characterization of chaura fruits (Gaultheria pumila): A native Chilean berry with commercial potential - Villagra-Quero, Evelyn (2017)
Background: For the first time, a morphometric characterization of chaura (Gaultheria pumila) fruits has been conducted between natural populations growing in the Villarrica National Park, Araucania Region, Chile. Chaura is a native Ericaceae from Chile that produces aromatic and tasty fruits which could be of agricultural interest. Results: To influence the decision for a further domestication of G. pumila, both the fruit sizes (indicator of productivity) and the nutritional properties of the fruits have been determined from different subpopulations. Samples were a total of 74 plants and 15 fruits per plant which were randomly harvested following its natural distribution around the Villarrica volcano. Altogether, fresh weight, shape, color, diameter in the pole and the equatorial dimensions were determined as phenotypic traits of the G. pumila fruits. Meanwhile the total soluble solids, anthocyanin and pectin contents were calculated as nutritional traits of the Chaura fruits. Results showed a high phenotypic diversity between the sampled population with three main fruit shapes and three predominant colors. The round shapes were the most abundant, whereas a significant correlation was found among fruit size with weight and color. The highest fresh weight (597.3 mg), pole diameter (7.1 mm) and equatorial diameter (6.5 mm) were estimated in the pink color fruits. Conclusions: The total amount of anthocyanin was higher in red fruits, while the maximum pectin content was obtained in the round white fruits. Overall results must pave the way for a further domestication and introduction of the Chaura species in the agro-productive system in Chile.